Failure to achieve a satisfactory cardiac outcome after isolated coronary surgery in low-risk patients. (23rd May 2020) - Rubino, Antonino S; Nicolini, Francesco; Tauriainen, Tuomas; Demal, Till; De Feo, Marisa; Onorati, Francesco; Faggian, Giuseppe; Bancone, Ciro; Perrotti, Andrea; Chocron, Sidney; Dalén, Magnus; Santarpino, Giuseppe; et al.
Abstract: OBJECTIVES: This study aims to investigate the incidence and determinants of major early adverse events in low-risk patients undergoing isolated coronary artery bypass grafting (CABG). METHODS: The multicentre E-CABG registry included 7352 consecutive patients who underwent isolated CABG from January 2015 to December 2016. Patients with an European System for Cardiac Operative Risk Evaluation (EuroSCORE) II of <2% and without any major comorbidity were the subjects of the present analysis. RESULTS: Out of 2397 low-risk patients, 11 (0.46%) died during the index hospitalization or within 30 days from surgery. Five deaths were cardiac related, 4 of which were secondary to technical failures. We estimated that 8 out of 11 deaths were potentially preventable. Logistic regression model identified porcelain aorta [odds ratio (OR) 34.3, 95% confidence interval (CI) 1.3–346.3] and E-CABG bleeding grades 2–3 (OR 30.2, 95% CI 8.3–112.9) as independent predictors of hospital death. CONCLUSIONS: Mortality and major complications, although infrequently, do occur even in low-risk patients undergoing CABG. Identification of modifiable causes of postoperative adverse events may be useful to develop preventative strategies to improve the quality of care of patients undergoing cardiac surgery. Clinical Trial Registration: NCT02319083 (https://clinicaltrials.gov/ct2/show/NCT02319083 ).